Search for AL amyloidosis risk factors using Mendelian randomization - Saunders, Charlie N; Chattopadhyay, Subhayan; Huhn, Stefanie; Weinhold, Niels; Hoffmann, Per; Nöthen, Markus M; Jöckel, Karl-Heinz; Schmidt, Börge; Landi, Stefano; Goldschmidt, Hartmut; Milani, Paolo; Merlini, Giampaolo; et al. (Blood advances, 2021)
In amyloid light chain (AL) amyloidosis, amyloid fibrils derived from immunoglobulin light chain are deposited in many organs, interfering with their function. The etiology of AL amyloidosis is poorly understood. Summary data from genome-wide association studies (GWASs) of multiple phenotypes can be exploited by Mendelian randomization (MR) methodology to search for factors influencing AL amyloidosis risk. We performed a 2-sample MR analyzing 72 phenotypes, proxied by 3461 genetic variants, and summary genetic data from a GWAS of 1129 AL amyloidosis cases and 7589 controls. Associations with a Bonferroni-defined significance level were observed for genetically predicted increased monocyte counts (P = 3.8 × 10-4) and the tumor necrosis factor receptor superfamily member 17 (TNFRSF17) gene (P = 3.4 × 10-5). Two other associations with the TNFRSF (members 6 and 19L) reached a nominal significance level. The association between genetically predicted decreased fibrinogen levels may be related to roles of fibrinogen other than blood clotting. be related to its nonhemostatic role. It is plausible that a causal relationship with monocyte concentration could be explained by selection of a light chain-producing clone during progression of monoclonal gammopathy of unknown significance toward AL amyloidosis. Because TNFRSF proteins have key functions in lymphocyte biology, it is entirely plausible that they offer a potential link to AL amyloidosis pathophysiology. Our study provides insight into AL amyloidosis etiology, suggesting high circulating levels of monocytes and TNFRSF proteins as risk factors.
Keywords: rizikové faktory; amyloidóza; Mendelian Randomization Analysis; mendelovská randomizace; Genome-Wide Association Study; lidé; primární amyloidóza; Risk Factors; Humans; Immunoglobulin Light-chain Amyloidosis; celogenomová asociační studie; Amyloidosis